2017
DOI: 10.5897/ajb2017.15898
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity among cultivated Pearl millet (Pennisetum glaucum, Poaceae) accessions from Benin, West Africa

Abstract: Simple sequence repeat (SSR) molecular markers were used for genetic diversity analysis and population structure of the cultivated Pearl millet in Benin, West Africa. In order to assess the level of genetic diversity, 14 polymorphic SSR markers were used to screen 114 accessions from different agroecological zones in Benin. SSR markers were found to reveal a total of 57 alleles with an average of 4.071 allele per locus. Genetic diversity index varied from 0.099 to 0.633 with an average of 0.405. The average ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
1
1
1
Order By: Relevance
“…Similarly, populations in Cluster I (As-As and Af-As) belonged to Group 3. Overall, the results showed poor differentiation of populations (As-As and Af-Af) from different geographical (Asian and African) regions which are supported by results of previous studies reporting the absence of any specific structuration among pearl millet accessions from different regions of West Africa (Adeoti et al, 2017) and among landraces of different regions of Sudan and West Africa (Bashir et al, 2015). Based on the clustering pattern, it can be inferred that the molecular GD between the 45 African and Asian populations did not show their clear grouping by geographical origin.…”
Section: Genetic Distance Cluster Analysis and Population Structure Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly, populations in Cluster I (As-As and Af-As) belonged to Group 3. Overall, the results showed poor differentiation of populations (As-As and Af-Af) from different geographical (Asian and African) regions which are supported by results of previous studies reporting the absence of any specific structuration among pearl millet accessions from different regions of West Africa (Adeoti et al, 2017) and among landraces of different regions of Sudan and West Africa (Bashir et al, 2015). Based on the clustering pattern, it can be inferred that the molecular GD between the 45 African and Asian populations did not show their clear grouping by geographical origin.…”
Section: Genetic Distance Cluster Analysis and Population Structure Analysissupporting
confidence: 84%
“…The relatively high gene diversity (H e = 0.75), observed heterozygosity (H o = 0.31), and mean number of alleles per locus (15 alleles), obtained in the current study, indicated the presence of considerable genetic variability among the 45 pearl millet populations under investigation. The present study detected a higher number of alleles and gene diversity than found in previous studies using SSRs in African pearl millet accessions (Adeoti et al, 2017;Diack et al, 2017). This might be due to use of more markers in our study and sampling of a larger number of individuals per population.…”
Section: Marker-based Genetic Variation In Pearl Millet Populationscontrasting
confidence: 65%
See 1 more Smart Citation
“…Pearl millet is one of the most important crops in the whole Sahelian region from Senegal to Sudan (Mariac et al 2006). This crop ranks second in Senegal (Bastos et al 2022) and fourth in Benin (Adeoti et al 2017). In Niger, pearl millet covers more than 65% of the total cultivated area (Mariac et al 2006).…”
Section: Food and Forage Interestmentioning
confidence: 99%
“…Pearl millet assumes a basic part in food security" [3]. It has amazing properties like high photosynthetic proficiency, high dry matter creation limit, early development, dry season resilience, the necessity of insignificant buy inputs, and general liberation from biotic and abiotic stresses [2,4]. "It can endure the most unfavorable agro-climatic circumstances where different harvests like sorghum and maize neglect to create monetary yields" [2].…”
Section: Introductionmentioning
confidence: 99%